Strategi pengambilan keputusan dalam menanggulangi penyalahgunaan narkoba pada remaja di kota Surabaya - Roihana; Juwita; Jamal, Adam (Journal Ilmu Sosial, Politik dan Pemerintahan, 2025)
Drug abuse in teenagers is one form of juvenile delinquency that is often encountered. For this reason, the role of the Surabaya City Government, the Surabaya National Narcotics Agency (BNN), the Surabaya City Education Office, and the Police are very much needed to tackle and prevent drug abuse among teenagers. This research aims to determine the strategies of the relevant agencies in making decisions to tackle drug abuse among teenagers in the city of Surabaya. This research uses a qualitative method using a descriptive approach. The results of this research show that cases of drug abuse among teenagers in Surabaya are increasing day by day. It is calculated from the large number of news broadcasts about drug abuse among teenagers in Surabaya. Factors that influence the occurrence of drug abuse in adolescents are family, environmental, and self-related factors. The most common reason teenagers use drugs is as an escape or distraction from the pressure of schoolwork or the problems they are facing, and drugs are even used as sedatives or sleeping pills to make it easier to fall asleep. The impact of drug abuse on teenagers can cause stress or depression, physical changes, and even death. Efforts made by several agencies in Surabaya to prevent and overcome drug abuse among teenagers, one of which is regular counseling and outreach.